Improving Household Environmental Health Through PHBS, Dagusibu, GeMa CerMat, and GerMas - Putri, Lusi Dwi; Soehardi, Fitridawati; Atmam, Atmam (Bisma : Bimbingan Swadaya Masyarakat, 2024)
Household health is a critical determinant of a quality life, particularly in areas that have already become slums, which should be a shared concern. This community service activity focused on providing counseling on clean and healthy living behaviors, along with proper medication usage. The goal was to enhance participants' knowledge on maintaining environmental health, managing medications properly, selecting and using medications correctly, and recognizing their efficacy and potential side effects. This intervention aimed to improve the community's overall health literacy and promote sustainable practices in drug management.